The Effect Of Breastfeeding On Stunting Incidence Among Low Birth Weight Babies - Eka Fitriyanti (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2025)
Breast Milk (BM) is the primary source of nutrition for newborns. Breast milk can be provided from birth, starting in the hospital and continuing throughout home care. Exclusive breastfeeding is rare among low birth weight (LBW) babies. This is due to parents' or caregivers' concerns about their baby's weight. Parents prefer to provide supplemental foods in addition to breast milk to accelerate weight gain. Low Birth Weight (LBW) babies who are given formula milk or other foods before 6 months of age are more susceptible to illness, making them more susceptible to illness. Low Birth Weight (LBW) babies can have serious health consequences, including stunting. The purpose of this study was to examine the effect of breastfeeding on stunting in low birth weight babies. A cross-sectional approach was used with purposive sampling. The results and discussion in this study revealed that not all babies were exclusively breastfed; some were supplemented with formula milk. Breast milk and formula milk intake affect the baby's nutrient absorption, thereby influencing their nutritional status. It appears that all LBW babies who do not receive breast milk will experience stunting in their growth and development.